Historical and Social Bases of Evil Symbols in the Avesta - Urazova Rano Tashpulatovna (Scientific Trends, 2024)
The article discusses the historical-social roots, moral-philosophical interpretation of the forces of Ahriman, the chief of evils in the Avesta. Scientific analyzes have been carried out to show that Ahriman’s giants, such as Apaosha, Saini, Buji, Bashi, Bushasp, Sij are the head of all the impurities in the world, the head of vices, the source of oppression, and they cause various diseases in humans (changes in human skin, pigmentation disorders, etc.). All the symbols of evil distract a person from the path of Truth and prevent him from doing good deeds. Zoroastrianism, on the other hand, demanded absolute faith in religion and its practice from the heart and vigilance. Therefore, all phenomena of existence, whether natural or social, are presented in the Avesta as a contrast between good and evil. In the Zoroastrian society, the responsibility assigned to a person is to be stable and firm in the path of goodness, to overcome any factors that distract him from goodness, not only to believe in the right of the good world of the creator, but also to serve the development of this world.
Keywords: zoroastrianism, Avesta, antropomorf, zoomorphic, Ahura Mazda, Axriman, Apush, Duruges, Buji, Saini, Baishi, Bushasp, Sij.